Griffin and Neal’s safety model: Determinants and components of individual safety performance in the Italian context - Toderi, Stefano; Gaggia, Andrea; Mariani, Marco Giovanni; Mancini, Gianpiero; Broccoli, Marco (La Medicina del Lavoro, 2015)
Introduction: Griffin and Neal’s model is a useful model to understand workers’ different safety behaviour (compliance and participation) starting from their mastery of safety procedures (safety knowledge) and the motivation to put them in place (safety motivation). Although the theoretical model has proven to be adequate and is widely used in research, two problems arise: 1) there is no Italian validation of the four scales measuring the key constructs of the model; 2) the hypothesis regarding the differential impact of the determinants on the components of safety performance produced mixed evidence. Objectives: The study had a twofold objective: 1) validate an Italian version of the four scales, primarily assessing their construct validity; 2) verify the relationships between the constructs according to the assumptions made within the theoretical model. Methods: The psychometric properties of the scales as well as the relationships between the constructs were investigated in a sample of 277 workers in the construction and logistics sectors, using questionnaires. The analyses were based on the use of structural equation modelling technique. Results: Results confirmed the validity and reliability of the Italian scales, showing indices that were both satisfactory and aligned with those from previous studies. The relationships between the constructs were substantially consistent with the safety model. Conclusions: The study provided a valid version of the scales measuring determinants and components of individual safe performance. Such scales can be appropriately used in the Italian context for the development of theoretical as well as practical contributions on work safety. The results suggest that interventions to increase overall safe performance should address both knowledge and motivation for safety.